2020
DOI: 10.1007/s10029-020-02167-w
|View full text |Cite
|
Sign up to set email alerts
|

Fasciocutaneous anterolateral thigh flaps for complex abdominal wall reconstruction after resection of enterocutaneous fistulas and the role of indocyanine green angiography: a pilot study

Abstract: Purpose No previous study reported the use of a fasciocutaneous anterolateral thigh (ALT) flap combined with a biological mesh for abdominal wall reconstruction (AWR) after enterocutaneous fistula (ECF) in a single-staged procedure and the use of Indocyanine Green Angiography (ICGA) intraoperatively. The purpose of this study was to determine the feasibility and safety of this procedure and to examine the added value of ICGA in minimizing postoperative complications. Methods A single-institution review of a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Only in an estimated 27–54% of patients can the fascia be closed directly during EAF takedown [24], but successful closure is a protective factor (4×) against EAF recurrence [9 ▪ ,39 ▪▪ ]. Although in the past some authors suggested a multistage approach with the definitive closure following in a second operation [54], single-stage repair is a viable and safe approach [9 ▪ ,18 ▪ ,28 ▪▪ ,55 ▪ ,56,57 ▪ ,58]. In order to reduce tension and facilitate closure of the fascial edges, a variety of techniques can be used (Table 1).…”
Section: Abdominal Wall Closure or Reconstructionmentioning
confidence: 99%
“…Only in an estimated 27–54% of patients can the fascia be closed directly during EAF takedown [24], but successful closure is a protective factor (4×) against EAF recurrence [9 ▪ ,39 ▪▪ ]. Although in the past some authors suggested a multistage approach with the definitive closure following in a second operation [54], single-stage repair is a viable and safe approach [9 ▪ ,18 ▪ ,28 ▪▪ ,55 ▪ ,56,57 ▪ ,58]. In order to reduce tension and facilitate closure of the fascial edges, a variety of techniques can be used (Table 1).…”
Section: Abdominal Wall Closure or Reconstructionmentioning
confidence: 99%